Defining and monitoring the quality of shared-use transportation facilities in parks and recreation areas. Issue 9 (21st October 2019) - Xiao, Xiao; Lu, Junyu; Manning, Robert; Reigner, Nathan
Abstract: Transportation networks in parks and recreation areas provide travelers recreation opportunities and often support multiple transportation modes (e.g., hiking, walking, biking). In recreation areas, the quality of transportation service may be monitored and evaluated differently than in traditional transportation contexts. However, few studies have examined approaches for defining and monitoring the quality of transportation service and recreation experiences. This study applies traffic monitoring models to monitor (1) the quality of transportation service through the Levels of Service (LOS) framework and (2) travelers' recreation experiences through the indicators and standards framework simultaneously on the Burlington Bike Path (BBP), a typical shared-use transportation recreation facility in Vermont. Results identify the temporal pattern of visitors use and the mode splits between cyclists and pedestrians. Moreover, study results show that the majority of travelers use the BBP for recreation or mixed purpose of recreation and commute. Study results build quantitative relationships between LOS and indicators and standards of quality that will help inform management of transportation in the context of recreation. The indicators and standards framework can help define the thresholds of acceptable levels of transportation service through the LOS framework. The relationships between LOS and the indicators and standards framework help build a robust and fully parameterized transportation planning and management framework for parks and recreation areas. Study results suggest quantitative guidelines that can be used to evaluate and monitor the quality of transportation performance for shared-use paths in parks and recreation areas.